2020
DOI: 10.1002/app.49131
|View full text |Cite
|
Sign up to set email alerts
|

Optical biosensor for catechol determination based on laccase‐immobilized anionic polyamide 6 microparticles

Abstract: This work presents the preparation, optimization, and testing of an enzymebased optical biosensor for catechol determination. The sensing area is attached to a glass support and contains: anionic polyamide 6 (PA6) porous microparticles supporting laccase from Trametes Versicolor, embedded in a Pebax ® MH1657 polymer binder that contains the optical indicator dye 3-methyl-2-benzothiazolinone hydrazone (MBTH), responsible for the optical transduction. The catechol analyte, after its enzymatic oxidation, forms o-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…The rest of the MP samples did not display resolved SAXS peaks. Such phenomenon was observed and studied previously with PA6 MP 19 . There, the absence of a Bragg peak was explained with the extensive micron‐sized porosity of the polyamide MP that makes negligible the density gradient between the crystalline and amorphous phases.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The rest of the MP samples did not display resolved SAXS peaks. Such phenomenon was observed and studied previously with PA6 MP 19 . There, the absence of a Bragg peak was explained with the extensive micron‐sized porosity of the polyamide MP that makes negligible the density gradient between the crystalline and amorphous phases.…”
Section: Resultssupporting
confidence: 58%
“…This process permitted the preparation of polyamide MP based on PA6, carrying elevated amounts of fillers, i.e., metal‐, ceramic‐, carbon allotrope or mixed payloads, as well as other polymer particles. Further investigations revealed that these hybrid MP can be used directly as supports for enzymes in biosensors or biocatalysts 19,20 or they can be transformed by melt processing into PA6‐based hybrids or laminate composites 21,22 . The procedure of ref.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Cano-Raya et al proposed a new laccase-based optical biosensor for catechol concentration determination [63]. Laccase from Trametes Versicolor is attached to anionic polyamide 6 (PA6) porous microparticles placed in a Pebax MH1657 polymer binder that includes MBTH that can produce a colored product when it interacts with the o-benzoquinone produced by the enzymatic reaction of catechol.…”
Section: Laccase-based Biosensorsmentioning
confidence: 99%
“…Their quite simple manufacturing procedure are highly fast and sensitive properties makes them very useful for catechol detection 7 . One of these biosensor compounds is the laccase enzyme, (benzenediol: oxygen oxidoreductases, EC 1.10.3.2), known as a multi‐copper oxidase and is commonly used in the construction of various biosensors 8–11 . To make enzyme molecules on the electrode surface more stable, efficient materials and immobilization strategies are necessary.…”
Section: Introductionmentioning
confidence: 99%